Dogs don't do ballet - Kemp, Anna.; Ogilvie, Sara, 1971- (London : Simon & Schuster Children's, 2010)
When the prima ballerina trips and falls during a performance of the Royal Ballet, Biff the dog finally gets his chance to prove that he is a ballet dancer.
Keywords: Ballet dancers -- Fiction; Dogs -- Fiction